Exploring the Nexus between Demand and Supply Side Competence, Supply Chain Agility, Process Compliances and Operational Performance - Luedech Girdwichai; Sudawan Somjai (International Journal of Supply Chain Management, 2019)
The main objective of the current study is to explore the nexus between demand and supply side competence, supply chain agility, process compliances and operational performance. Firstly, the study has examined the direct relationships among the supply side competence, demand side competence, supply chain agility, and operational performance. Secondly, the study has examined the mediating role of the supply chain agility in the relationship between demand and supply side competence and operational performance. Lastly, the moderating role of process compliances in the relationship between demand and supply side competence and supply chain agility is examined. The current study has used SEM-PLS as statistical tool to answer the research questions raised in this study and research objectives envisaged in the current study. The findings of the study have provided support to the theoretical foundation and proposed hypothesis of the current study. Current study will be helpful for policymakers and practitioners in understanding the issues demand and supply side competence, supply chain agility, process compliances and operational performance.